A method for automatic analysis Table of Contents in Chinese books. Issue 3 (21st September 2015) - Chen, Jing; Lu, Quan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose a novel method to analyze Table of Contents (TOC) in Chinese books automatically based on the hierarchy organization rules which gained by investigation. Design/methodology/approach – This paper analyzed the main literature in this field first, then hierarchy organization rules of Chinese book TOC were generated and the method parsing TOC automatically based on these rules was proposed. A prototype system implementing the method was also developed. The method was evaluated through processing a corpus on the prototype system, and the results were checked with calculation of precision and recall. Findings – The experiment result illustrated the superiority (extensive application, recall is 95.34 percent and precision is 94.44 percent) of the method. Practical implications – The result can help Chinese libraries deal with electronic texts from four aspects. First, it can be used to complement or enhance current digitization and optical character recognition methods and cut the financial and labor cost of Chinese libraries. Second, it can help libraries to keep information on indexing words as well as chapters, sections and subsections in Chinese book databases, which ensures easy retrieval and extract any intended portion as demanded by user. Third, it helps to enrich the services and then enhances the user experiences in Chinese libraries. Fourth, it improves the specification and policy of digitalizing Chinese books. Originality/value – The paper provided insight into the hierarchy organization of TOCs in Chinese books, the method based on the rules has extensive application than other methods. This method for Chinese book TOC automatic analysis is also as reference for English book TOC automatic analysis.